2005
DOI: 10.1093/hmg/ddi067
|View full text |Cite
|
Sign up to set email alerts
|

Expanded polyglutamine peptides disrupt EGF receptor signaling and glutamate transporter expression in Drosophila

Abstract: Huntington's disease (HD) is a late onset heritable neurodegenerative disorder caused by expansion of a polyglutamine (polyQ) sequence in the protein huntingtin (Htt). Transgenic models in mice have suggested that the motor and cognitive deficits associated to this disease are triggered by extended neuronal and possibly glial dysfunction, whereas neuronal death occurs late and selectively. Here, we provide in vivo evidence that expanded polyQ peptides antagonize epidermal growth factor receptor (EGFR) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 73 publications
6
60
1
3
Order By: Relevance
“…Although there may be several possibilities that may explain the SCA14 disease pathology, defects in MARCKS-dependent cell adhesion or spreading may explain the neurodegenerative phenotype. The role of ERK signaling in neurodegenerative disorders is more complex, because both protective and deleterious roles for ERK activation in neuronal cells have been described (Apostol et al, 2006;Colucci-D'Amato et al, 2003;Lievens et al, 2005). The diversity of ERK activation is not surprising, because the pathway integrates various signals depending on the cellular context, including cell proliferation, differentiation, migration and survival (Bhalla and Iyengar, 1999;Chuderland and Seger, 2005;Hetman and Gozdz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be several possibilities that may explain the SCA14 disease pathology, defects in MARCKS-dependent cell adhesion or spreading may explain the neurodegenerative phenotype. The role of ERK signaling in neurodegenerative disorders is more complex, because both protective and deleterious roles for ERK activation in neuronal cells have been described (Apostol et al, 2006;Colucci-D'Amato et al, 2003;Lievens et al, 2005). The diversity of ERK activation is not surprising, because the pathway integrates various signals depending on the cellular context, including cell proliferation, differentiation, migration and survival (Bhalla and Iyengar, 1999;Chuderland and Seger, 2005;Hetman and Gozdz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in a Drosophila model of HD that selective overexpression of Huntingtin in glia can have a remarkable influence on the whole brain and on disease progression. 42 Concerning the possible direct involvement of glutamate receptors in the phenomenon, it has been demonstrated that this neuroprotection is not due to a reduced number of Figure 2 Comparison of Htt domain structure of six HD mouse models that show resistance against excitotoxicity. Different models cover different parts of Htt (full-length Htt shown in orange, covered parts shown in green, yellow, blue and white) (not in scale).…”
Section: Possible Mechanisms Involved In Huntingtin-mediated Resistancementioning
confidence: 99%
“…On notera que les mouches meurent aussi vite lorsque la protéine pathogène est exprimée dans les cellules gliales avec repo ou dans les neurones avec le promoteur du gène elav. Sur le plan cellulaire, la présence de la protéine Huntingtine mutée dans les cellules gliales réduit progressivement l'expression de EAAT1, l'unique transporteur de glutamate chez la drosophile [18], mais n'affecte pas significativement la survie de ces cellules [19]. Ces données apportent des arguments en faveur d'une action directe de la Huntingtine mutée sur le fonctionnement des astrocytes dans la chorée de Huntington.…”
Section: Les Astrocytes Dysfonctionnent Dans La Chorée De Huntingtonunclassified
“…Nous avons donc fait l'hypothèse que la présence de longues chaînes de résidus glutamine modifierait l'expression de gènes essentiels pour le fonctionnement du système nerveux en altérant, entre autres, la voie de signalisation du récepteur à l'EGF dans les cellules gliales. En accord avec cette idée, l'expression de la protéine Huntingtine mutée in vivo dans les cellules gliales de drosophile prévient l'augmentation des taux de transporteur du glutamate induite par l'activation du récepteur à l'EGF, mais pas par l'activation de Ras ou ERK [19]. Ces données sont de plus étayées par des observations obtenues au niveau de l'oeil composé de drosophile, dont le développement dépend étroitement de la voie de signalisation du récepteur à l'EGF.…”
Section: Les Mécanismes Moléculaires Du Dysfonctionnement Des Astrocytesunclassified
See 1 more Smart Citation